The potential of hydrophyte plants for remediation of liquid waste of tapioca factory - E R Indrayatie; E Arisoesilaningsih (Journal of Degraded and Mining Lands Management, 2015)
The potential role of a macrohydrophyte plant (Vetivera zizanioides) and four semihydrophyte plants (Ipomoea aquatica, Cyperus iria, Commelina nudiflora, Oryza sativa) as remediators of liquid waste of tapioca industry was tested in a glasshouse for 35 days under conditions that resemble to wet and polyculture systems. Results showed that all type of plants grew normally on media containing tapioca liquid waste. Total biomass of I. aquatica and polyculture grown in wet conditions were 32.35 g and 38.44 g, respectively. These were higher than those of control (30.53 g and 36.39 g). Those of V. zizanioides, C. iria, C. nudiflora and O. sativa were inversely observed. However, V. zizanioides showed the highest tolerance index value (120.99%) compared to that of I. aquatica (91.21 %), C. iria (56.62 %), C.nudiflora (89.63 %), O. sativa (83.13 %), and polyculture (62.25 %).